PENGARUH DEBIT TERHADAP UNJUK KERJA ALAT PENUKAR KALOR DAN PENURUNAN SUHU RUANGAN - Mirmanto, Mirmanto; Sayoga, I Made Adi; Zulkarnain, Zulkarnain (Universitas Mataram, 2016)
ABSTRACTDue to population growth, industry advance and rapid development, fresh and comfortable air may be difficult to get. Conditioning the air to get comfort environment may be a basic demand for people, but the prices of the device and its operation for this purpose are expensive. This research tries to solve this problem but it is just only to know the capability of the heat exchanger to transfer/ absorb heat and is not to cool the room to be below the ambient temperature. The working fluid used was clean water and the heat exchangers employed were parallel and serpentine which were made of copper pipes with a diameter of 1/4 inch and 1/2 inch (for the header). The volumetric flow rates used were 300 ml/minutes, 400 ml/minutes and 500 ml/minutes. While the heat that should be absorbed by the water from the room is 50 W, 100 W and 150 W. The results show that the effect of volumetric flow rate on heat exchanger performance and room temperature is insignificant. From the pressure drop results, the parallel pipe heat exchanger has lower pressure drops while the serpentine has higher pressure drops.